The Gods are broken! : the hidden legacy of Abraham - Salkin, Jeffrey K., 1954- (UPCC book collections on Project MUSE., 2013)
The story of Abraham smashing his father's idols might be the most important Jewish story ever told and the key to how Jews define themselves. In a work at once deeply erudite and wonderfully accessible, Rabbi Salkin conducts readers through the life and legacy of this powerful story and explains how it has shaped Jewish consciousness. Offering a radical view of Jewish existence, this book views the story of the young Abraham as the "primal trauma" of Jewish history, one critical to the development of a certain Jewish comfort with rebelliousness and one that, happening in every generation, has helped Jews develop a unique identity. The author shows how the story continues to reverberate through the ages, even in its connection to the phenomenon of anti-Semitism. This work - combining biblical texts, archaeology, rabbinic insights, Hasidic texts (some never before translated), philosophy, history, poetry, contemporary Jewish thought, sociology, and popular culture - is nothing less than a journey through two thousand years of Jewish life and intellectual endeavor.